Harmonizing Faith and Culture: The Role of Bubur Keselamatan in Madurese Identity - Anas Muzakki; Rahmat Rahmat; Adam Has Wildan; Wahidah Zein Br Siregar (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study explores how Islamic values are integrated into local cultural practices through the bubur keselamatan tradition in Lerpak Bangkalan, Madura. It highlights how spiritual values, symbolism, and moral teachings are embedded in this tradition, reflecting the harmonious coexistence of Islam and indigenous Madurese culture. Data were collected using qualitative methods, including in-depth interviews, participatory observation, and documentation, with a focus on elements such as communal prayers, the symbolic use of odd numbers, and the value of patience demonstrated during the cooking process. The findings reveal that the bubur keselamatan tradition serves as a medium for expressing gratitude to Allah while preserving local wisdom. It exemplifies how Islamic principles, such as obedience to God and patience, are seamlessly integrated into cultural practices, creating unique forms of religious expression. For instance, the use of odd numbers in this tradition symbolizes spiritual significance that transcends cultural boundaries, demonstrating how universal values are reflected in local customs. The study contributes to religious and cultural anthropology by demonstrating the dynamic interaction between religion and culture in rural Indonesian society. It underscores the importance of preserving local traditions as tools for maintaining cultural identity and fostering social cohesion. Additionally, it highlights the relevance of the bubur keselamatan tradition as a model for understanding how universal Islamic values can coexist with local customs, offering valuable lessons for addressing cultural preservation challenges amid globalization. These findings emphasize the need to safeguard local wisdom to ensure the continuity of cultural heritage and strengthen national character.